Potential Opioid-Related Adverse Drug Events Are Associated With Decreased Revenue in Hip Replacement Surgery in the Older Population. (25th March 2020) - Baker, Justin; Brovman, Ethan Y.; Rao, Nikhilesh; Beutler, Sascha S.; Urman, Richard D.
Introduction: Opioid-related adverse drug events (ORADEs) are an increasingly recognized complication associated with the common prescription of opioids after orthopedic surgery. In this study, we attempted to understand how potential ORADEs following hip replacement surgery in older patients affected hospital length of stay, hospital revenue, and their association with specific risk factors and clinically relevant diseases occurring during hospitalization. Methods: We conducted a retrospective study using the Centers for Medicare and Medicaid Services Administrative Database to analyze Medicare discharges after hip replacement surgery to identify potential ORADEs. The impact of potential ORADEs on mean hospital length of stay (LOS) and hospital revenue was analyzed. Results: The potential ORADE rate in patients who underwent hip replacement surgery was 8.6%. The mean LOS for discharges with a potential ORADE was 1.41 days longer than that for discharges without an ORADE. The mean hospital revenue per day with a potential ORADE was US$1708 less than without an ORADE. Potential ORADEs were also found to be strongly associated with poor patient outcomes such as pneumonia, septicemia, and shock. Discussion: Potential ORADEs in hip replacement surgery in older patients are associated with longer hospitalizations, decreased hospital revenue per day, certain patient risk factors, and clinically relevant diseases occurring during hospitalizations. Our finding of an association between potential ORADEs and decreased hospital revenue per day may be attributed to the management of these adverse events, as a patient may need to undergo additional testing, may need additional treatment regimens, and may need a higher level of care. Conclusion: By reducing the use of opioids and employing a multimodal analgesic approach, we may improve patient care, decrease hospital lengths of stay, and increase hospital revenue